2015
DOI: 10.2527/jas.2014-8297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supplemental protein source offered to primiparous heifers during gestation on II. Progeny performance and carcass characteristics

Abstract: A 3-yr study using primiparous crossbred beef heifers (n = 114) was conducted to determine the effects of protein supplement during late gestation on progeny performance and carcass characteristics. Pregnant heifers were stratified by heifer development system, initial BW, and AI service sire and placed in an individual feeding system. Heifers were offered meadow hay (8 to 11% CP) from early November to mid-February and provided no supplement (CON; n = 37), 0.83 kg/d (DM basis) of a dried distillers grains wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…Differences in birth weight due to calf sex is likely the cause of increased calving difficulty in those heifers giving birth to bull compared with heifer calves and has been noted previously in the literature (Burfening et al, 1978;Berger et al, 1992;Eriksson et al, 2004). Subsequent postnatal calf performance through slaughter is reported elsewhere (Summers et al, 2015).…”
Section: Calving and Subsequent Pregnancy Resultsmentioning
confidence: 74%
“…Differences in birth weight due to calf sex is likely the cause of increased calving difficulty in those heifers giving birth to bull compared with heifer calves and has been noted previously in the literature (Burfening et al, 1978;Berger et al, 1992;Eriksson et al, 2004). Subsequent postnatal calf performance through slaughter is reported elsewhere (Summers et al, 2015).…”
Section: Calving and Subsequent Pregnancy Resultsmentioning
confidence: 74%
“…Such perturbations to placental development may reduce foetal growth due to decreased nutrient transport via the placenta (Sullivan et al ., 2009c) generating a decrease in birth weight (Perry et al ., 1999; Micke et al ., 2010c), or alternatively dichotomous placental development (as in the LH group) may be attendant to increased birth weight and associated dystocia.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that gestational dietary regimens effectively alter placental signalling hormones (Sullivan et al ., 2009c; Summers et al ., 2015). These may act to signal foetal skeletal muscle IGF messenger RNA (mRNA) expression and fibre development during the first two trimesters of gestation as previously shown in foetal skeletal sheep muscle where nutritional restriction increased IGF-2 mRNA expression (Brameld et al ., 2000) and increased IGF receptor activity (Symonds et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited data available assessing the effects of poor maternal diet on offspring RFI. Offspring of primiparous beef heifers supplemented with rumen-undegraded protein during late gestation demonstrated decreased RFI (increased efficiency) compared with offspring of unsupplemented dams during the feedlot period (Summers et al, 2015). However, Meyer et al (2014) found no differences in RFI, DMI, G:F, or ADG during finishing in steers or heifers born to cows that were nutrient restricted (70% of control) during early gestation and midgestation.…”
Section: Musclementioning
confidence: 93%